2016
DOI: 10.1109/tns.2016.2550503
|View full text |Cite
|
Sign up to set email alerts
|

A Study of a Mini-Drift GEM Tracking Detector

Abstract: Abstract-A GEM tracking detector with an extended drift region has been studied as part of an effort to develop new tracking detectors for future experiments at RHIC and for the Electron Ion Collider that is being planned for BNL or JLAB. The detector consists of a triple GEM stack with a small drift region that was operated in a mini TPC type configuration. Both the position and arrival time of the charge deposited in the drift region were measured on the readout plane which allowed the reconstruction of a sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…However, this non-linearity can be corrected for by measuring the response of the pad in very fine steps. In order to measure this, the detector was configured as a "minidrift" detector with a 1.6 mm drift gap above the GEM [4,5] and scanned across the chevron direction using a highly collimated X-ray source. Figure 7 shows the measured response of the detector as a function of the source position and the differential non-linearity.…”
Section: Electrostatic Field Simulationsmentioning
confidence: 99%
“…However, this non-linearity can be corrected for by measuring the response of the pad in very fine steps. In order to measure this, the detector was configured as a "minidrift" detector with a 1.6 mm drift gap above the GEM [4,5] and scanned across the chevron direction using a highly collimated X-ray source. Figure 7 shows the measured response of the detector as a function of the source position and the differential non-linearity.…”
Section: Electrostatic Field Simulationsmentioning
confidence: 99%
“…Later, MWPCs and GEMs were read out with parallel zigzag strips and good spatial resolutions were achieved [2,3]. This was confirmed in more recent studies which showed that the spatial resolution of a small GEM detector with parallel zigzag strip or zigzag pad readout can approach 70 µm [4,5]. We subsequently introduced radial zigzag strips to read out trapezoidal large-area GEM detectors [6], which are intended for tracking systems at future experiments, e.g.…”
Section: Introductionmentioning
confidence: 65%
“…In our previous studies [5,6], we observed a non-linear relation between incident particle position and hit position measured from charge sharing among radial zigzag readout strips. This paper aims at quantifying the non-linear response of our previous zigzag designs and to demonstrate an improved zigzag design that has a linear response.…”
Section: Introductionmentioning
confidence: 86%
“…Roughly half of all the clusters of charge collected by each pad-row fired a single pad, so interpolating the hit position was not possible. This resulted in a significant degradation of the single point resolution for pad rows with only one pad firing [9]. For this reason, tracks were only reconstructed for events where at least three pad-rows consisted of 2 or more fired pads.…”
Section: A Tpc Detectormentioning
confidence: 99%